The Influence of Higher Order Thinking Skills (HOTS) Learning Model and Learning Motivation on Achievement in Learning Islamic Cultural History - Yunus, Mahmud (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The primary objectives of this study were threefold: firstly, to assess the impact of the Higher-Order Thinking Skills (HOTS) learning model on the academic performance of Islamic Education (Islamic Cultural History) students at MIN 2 Pemalang; secondly, to analyze the influence of learning motivation on the academic achievement of Islamic Cultural History students at MIN 2 Pemalang; and finally, to investigate the combined effect of the HOTS learning model and learning motivation on the academic performance of Islamic Cultural History students at MIN 2 Pemalang. This research adopts a quantitative approach with a quasi-experimental design. The study's population consists of students from both class V.B and class V at MIN 2 Pemalang during the academic year 2019/2020. Data collection involves the use of a questionnaire instrument to gauge learning motivation and student test results to measure academic achievement. The gathered data is subjected to statistical analysis, including calculating the mean correlation, using SPSS 21.0 software, and employing a t-test with a predetermined significance level. The study's findings are as follows: 1) The HOTS learning model significantly influences the academic achievement of Islamic Cultural History. 2) Learning motivation significantly impacts the academic performance of Islamic Cultural History. 3) The combined effect of the HOTS learning model and learning motivation significantly influences the academic achievement of Islamic Cultural History.